2023
DOI: 10.1111/pde.15327
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate for inflammatory skin disease in pediatric patients: Consensus treatment guidelines

Abstract: Methotrexate (MTX) is a readily accessible drug, first used in 1948 and employed for a wide variety of indications since then. However, despite widespread off‐label use, FDA labeling does not include approved indications for the use of MTX for many inflammatory skin diseases in pediatric patients, including morphea, psoriasis, atopic dermatitis, and alopecia areata, among others. Without published treatment guidelines, some clinicians may be hesitant to use MTX off‐label, or uncomfortable prescribing MTX in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 254 publications
1
5
0
Order By: Relevance
“…We found that the risks of AEs were higher in children compared to adults (Table 3), which reflected higher AEs incidence rates in this population. In fact, high‐incidence rates (as high as 25–50%) for the same adverse effects were reported when safety data of studies using MTX for inflammatory skin diseases in the paediatric population were pooled 44 . Besides, we found that children had a seven‐fold lower rate of treatment discontinuation due to side effects compared to adults, which indicates that the AEs did not call for MTX termination.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…We found that the risks of AEs were higher in children compared to adults (Table 3), which reflected higher AEs incidence rates in this population. In fact, high‐incidence rates (as high as 25–50%) for the same adverse effects were reported when safety data of studies using MTX for inflammatory skin diseases in the paediatric population were pooled 44 . Besides, we found that children had a seven‐fold lower rate of treatment discontinuation due to side effects compared to adults, which indicates that the AEs did not call for MTX termination.…”
Section: Discussionsupporting
confidence: 58%
“…In fact, high-incidence rates (as high as 25-50%) for the same adverse effects were reported when safety data of studies using MTX for inflammatory skin diseases in the paediatric population were pooled. 44 Besides, we found that children had a seven-fold lower rate of treatment discontinuation due to side effects compared to adults, which indicates that the AEs did not call for MTX termination. For example, the increases in transaminases levels observed in the studies for children [37][38][39][40] predominantly had a mild/transient nature or the 11 haematologic abnormalities observed in the paediatric study of reference 37 were transient (see footnotes of Table 2).…”
Section: Discussionmentioning
confidence: 72%
“…Since information regarding doses and monitoring in infants and toddlers with AD is sparse, we compared our data with the consensus treatment guidelines for MTX in pediatric patients with inflammatory skin diseases [ 27 ]. Nevertheless, this consensus does not provide specific dosage recommendations for AD in pediatric patients, and a starting dosage ranging from 0.3 to 0.5 mg/kg was recommended along with a maintenance dose of less than 1 mg/kg/week.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of relative or absolute contraindications regarding the administration of MTX that we present in Table 2 [31].…”
Section: Methotrexate-pharmacological Aspectsmentioning
confidence: 99%